Case report: 11-ketotestosterone may potentiate advanced bone age as seen in some cases of Wiedemann-Steiner Syndrome - Buchanan, Katherine; Greenup, Erin; Hurst, Anna C. E.; Sunil, Bhuvana; Ashraf, Ambika P. (Frontiers in Endocrinology, 2022)
Context: Wiedemann-Steiner Syndrome (WSS) is a genetic disorder associated with an array of clinical phenotypes, including advanced bone age and short stature. 11-ketotestosterone (11KT) is a member of the group known as 11-oxygenated C19 androgens that are implicated in premature adrenarche. Case Description: Case 1: The patient is a 3 year and 11-month-old female diagnosed with WSS due to deletion of KMT2A detected on CGH microarray. At two years and 11 months, imaging revealed an advanced bone age. We obtained an 11KT level on this patient. 11KT in case 1 was elevated at 26.3 ng/dL, while the normal reference range is 7.3-10.9 ng/dL and the reference interval for premature adrenarche is 12.3-22.9 ng/dL, The repeat 11KT at follow up (chronological age 4 years and 6 months) was still elevated at 33.8 ng/dL Case 2: A second child with WSS and a 5kb intragenic KMT2A deletion was evaluated at 11 months of age; his 11KT was 4.5 ng/dL. Conclusions: The elevated 11KT may indicate maturational changes related to increasing adrenal gland androgenic activation and may explain the advanced bone age seen in some patients with WSS. To our knowledge, this is the first case report that describes 11KT as a bioactive androgen potentially causing bone age advancement in WSS. Lack of elevation of 11KT in the second child who is an infant suggests increasing androgenic precursors and metabolites related to premature adrenarche may need to be longitudinally followed.